PERANCANGAN SIKLUS PRODUKTIVITAS SEBAGAI STRATEGI PENINGKATAN KINERJA DAN DAYA SAING PT X (Studi Pada Perusahaan Manufaktur Packaging) - Endang Suhendar (LPPM, 2010)
P.T. X is a plastic packaging company are always trying to maintain customer and able to compete with rival firms in order to be able to maintain Suistainabillity. One indicator that the company is able to retain customers and to be able to maintain Suistainabillity is productivity level. Productivity cycle which introduced by David J Sumanth expected able to improve the productivity P.T X. Productivity to be measured, analysed, planned and improved are the parsial productivity of labour, material productivity, productivity of energy and capital productivity. Products that are considered to give the greatest konribusi contribution in productivity are Noodle, Shampoo, Oilpack and Saucepack. Through the sequential steps in the implementation cycle obtained productivity targets to increase the productivity of labor productivity is expected to reach 49.52, to reach the productivity of materials 1.36, to achieve energy productivity of the last to 261.90 and the productivity of capital is expected to reach 113.44. With this value the company expected a company can improve its performance and competitiveness. Keywords : Productivity, Productivity Cycle, Performance, Competitivenes, Sumanth